Using Wood Chips for Mulch, Yard Care and the Environment - Warminski, Norman C.; Neier, Bob; Upham, Ward (My University, 1998)
This publication describes proper landscaping that will benefit homeowners.
MF2133_1998_11
Keywords: MF2133; Lawn and Garden; Environment and Natural Resources; MF